Decolonizing global health curriculum: from fad to foundation - Kalbarczyk, Anna; Perkins, Sylvie; Robinson, Sabreena N.; Ahmed, Mahnoor K. (Frontiers in Education, 2023)
Introduction Increasing calls have been made to decolonize global health education but there has been a lack of consensus and clarity on how this should be done. We conducted a qualitative study to understand current educational programs and curricula that aim to educate public health and allied health students to increase awareness of how colonialist structures of power influence current global health practice and provide students with tools to decolonize global health. Our goal is to inform related curriculum development and provide recommendations. Methods We conducted key-informant interviews with 14 study coordinators and faculty from institutions of higher learning with global health programs who are involved in developing educational approaches. All interviews were audio recorded, transcribed, and analyzed using an ‘up from the data’ approach. Results Participants varied in their understanding of decolonizing global health and recognized that there is a lack of guidance in the field; this has an impact on how curriculum is developed and taught. Participants described a range of decolonizing global health educational activities in the classrooms and in applied learning activities. Most programming was situated in Diversity, Equity, and Inclusion Initiatives and participants did not always feel this was the best ‘home’ for such work; to some this reflected a lack of institutional support. Other institutional barriers included lack of protected time for faculty and limited budgets for speaker honoraria, co-creation, and related teaching expenses. Discussion Institutes of higher learning can play an important role, either positively or negatively, in decolonizing global health education. At a minimum such institutions should financially support faculty to incorporate decolonizing global health in their pedagogy and strengthen scholarship towards common understandings. More substantive institutional support is needed however to meaningfully transform institutional relationships that actively support equitable partnerships, co-creation, and responsiveness to local community priorities.